2017
DOI: 10.1121/1.4977583
|View full text |Cite
|
Sign up to set email alerts
|

Listeners' attitudes toward accented talkers uniquely predicts accented speech perception

Abstract: Listeners' sensitivity to indexical information influences their ability to perceive and remember speech, but it is less clear if listeners' subjective ratings of talker characteristics also impact speech perception ability. The present experiment tested the increase in variance accounted for by listeners' ratings of foreign accented talkers' manner of speaking and of the talkers themselves beyond the variance already accounted for by listeners' age, executive function, and hearing thresholds. Adding listeners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Many studies investigating this issue have asked participants to listen to an audio signal accompanied by pictures of talkers with different apparent ethnic or racial identities. Results have shown that listeners interpret the same speech signal differently, depending upon whether they believe the speaker is foreign-born or native (e.g., Rubin, 1992;McGowan, 2015;Ingvalson et al, 2017).…”
Section: Integrating Cues About the Speakermentioning
confidence: 99%
“…Many studies investigating this issue have asked participants to listen to an audio signal accompanied by pictures of talkers with different apparent ethnic or racial identities. Results have shown that listeners interpret the same speech signal differently, depending upon whether they believe the speaker is foreign-born or native (e.g., Rubin, 1992;McGowan, 2015;Ingvalson et al, 2017).…”
Section: Integrating Cues About the Speakermentioning
confidence: 99%
“…These findings are also in line with the results of Chakraborty and colleagues (2019), which reported that the students and professionals in speech-language pathology presented with more unbiased beliefs about persons with accented speech compared to high schoolers. Individuals with higher education tend to have more exposure to people with diverse language backgrounds, which may lead to the listeners’ positive attitude toward accented speech (Ingvalson et al, 2017; Kang & Rubin, 2009; Munro et al, 2006). This may account for why individuals with bachelor’s degrees or higher were more likely to view the SA and RA samples as acceptable for an SLP.…”
Section: Discussionmentioning
confidence: 99%
“…Perception of speech is influenced by listeners’ physical ability such as age (Adank & Janse, 2010) and hearing acuity (Gordon-Salant et al, 2010). Other factors related to listeners’ experience are listeners’ attitude (Ingvalson et al, 2017; Kang & Rubin, 2009), familiarity (Munro et al, 2006), prior knowledge of particular accents’ characteristics (e.g., Clopper & Pisoni, 2004), and the speaker’s or the listener’s language background (Bent & Bradlow, 2003). Environmental factors such as context (Carlson & McHenry, 2006) and noise (Gordon-Salant et al, 2010) may affect the listeners’ perception of accented speech as well.…”
Section: Listener’s Factors Influencing the Perception Of Accented Sp...mentioning
confidence: 99%
“…Defining successful Lx acquisition this way justifies characterizations of "non-native-accented" input as having a "negative effect" (Young-Scholten, 1995), as well as characterizations of variation in multilinguals' productions as "mispronunciations" (e.g., Bosch & Ramon-Casas, 2011;Llompart & Reinisch, 2021), as "less accurate" than native speakers' productions (Hayes-Harb & Masuda, 2008) or "inauthentic" (Flege & Liu, 2001). This ideology has, of course, been challenged (e.g., by Falkert, 2016;Golombek & Jordan, 2005), often in the context of promoting intelligibility (as opposed to native-likeness) as a goal for Lx learners (e.g., Levis, 2005Levis, , 2020, though it is important to note that the intelligibility construct is also not devoid of social influence and bias (see, e.g., Babel & Russell, 2015;Ingvalson et al, 2017). Many scholars have further challenged the underlying native/non-native speaker dichotomy altogether (e.g., Cheng et al, 2021;Kabel, 2009;Moussu & Llurda, 2008), highlighting the ways in which racism and the racialization of "non-native" teachers of English underlie ideologies of preference for nativespeaker language teachers (Ramjattan, 2019a(Ramjattan, , 2019b.…”
Section: Discussionmentioning
confidence: 99%